THE IMPACTS OF OIL PRICE SHOCKS ON INDONESIAN GDP AND CPI INFLATION - , Dwi Kesumawati Riyanto; , Dr Yoichi Okita ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper studies the impact of oil price shocks on Indonesian GDP and CPI inflation, distinguishing between the period during which Indonesia was a net oil-exporting country and when Indonesia became a net oil-importing country. This paper also analyzes the asymmetric responses to oil price changes. Using impulse response function on VAR model, this paper find that in the first period the shock in real oil price positively affects GDP and it negatively affects CPI inflation, and in the second period, the shock in real oil price positively affects GDP as well as it positively affects CPI inflation. By using asymmetric response approaches, this paper find that the Indonesian economy is more vulnerable to the decreasing real oil price than that to increasing real oil price. It is evident that asymmetric responses exist between the impact of oil price increase and that of oil price decrease. These findings suggest that because oil price has significant impact on Indonesian real economic activities, the Indonesian government should manage the production and consumption of oil, speed up efforts to shift from reliance on oil as a source of energy to that on gas, develop alternative energy resources, and encourage a change of industrial structure from resource-based industries to high value-added ones.